Assessment of olfactory status in allergic and non-allergic rhinitis patients. - Mann, S; Maini, S; Nageswari, K; Mohan, H; Handa, A (2002)
A study undertaken to assess the olfactory acuity in allergic (group I) and non-allergic rhinitis (group II) patients in comparison with age and sex matched controls (group III). Patients presenting with atleast three of the five cardinal symptoms of rhinitis i.e. rhinorrhoea, sneezing, itching, headache and nasal obstruction were grouped as non-infective rhinitis and further divided into allergic rhinitis (group I, n = 20) and non-allergic rhinitis (group II, n = 20) based on nasal smear cytology positivity or negativity for eosinophils respectively. Detailed Ear, Nose and Throat examination was carried out in both the groups and peripheral blood samples were analysed for total, differential leukocyte and absolute eosinophil counts using standard techniques. In all the three groups the olfactory thresholds for 5 odorants i.e. musk (M), formalin (F), camphor (C), asafoetida (A, 10% aqueous solution) and oil of peppermint (P, 20%) were evaluated for testing musky, pungent, camphorous, putrid and minty odours respectively by the method described by Elsberg and Levy for quantitative olfactometry. The results indicated elevation of olfactory thresholds (delta %, calculated taking control values as 100%) for 4 or 5 odorants in group I and group II patients respectively as compared with controls (group I: delta % for P--89.6%; M--116.4%; A--55.8%; P < 0.001; C--73.1%; P < 0.02; F--26.6% N.S.; group II: P--96.9%; M--99.3%, P < 0.01 for both; A--66.8%; C--102.7%, P < 0.001; F--42%, P < 0.05). In the non allergic rhinitis group the magnitude of the olfactory loss was more severe except for the odorant musk. Further interpretations as per gender based specificities revealed more severe olfactory loss in males of both the groups for the odorants peppermint and musk and moderately severe olfactory loss for formalin and camphor as compared to females. However, for the odorant asafoetida females showed greater olfactory loss than males in both the groups (delta % 73.38% versus 52% in group I and 81.29% versus 69.7% in group II).